2014
DOI: 10.1021/ja508280n
|View full text |Cite
|
Sign up to set email alerts
|

Thermochromic and Photoresponsive Cyanometalate Fe/Co Squares: Toward Control of the Electron Transfer Temperature

Abstract: Two structurally related and photoresponsive cyanide-bridged Fe/Co square complexes, {Fe2Co2}, are reported: {[(Tp(Me))Fe(CN)3]2[Co(bpy)2]2[(Tp(Me))Fe(CN)3]2}·12H2O (2) and {[(Tp(Me))Fe(CN)3]2[Co(bpy)2]2[BPh4]2}·6MeCN (3), where Tp(Me) and bpy are hydridotris(3-methylpyrazol-1-yl)borate and 2,2'-bipyridine, respectively. Through electrochemical and spectroscopic studies, the Tp(Me) ligand appears to be a moderate σ donor in comparison to others in the [NEt4][(Tp(R))Fe(III)(CN)3] series [where Tp(R) = Tp, hydri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
149
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(161 citation statements)
references
References 68 publications
9
149
0
3
Order By: Relevance
“…Therefore the Fe II site is stabilized. The two new squares 17 and 18 obtained with this new precursor display T 1/2 at 244 and 230 K, respectively, well above the T 1/2 at of 177 K found in the original square 2 . This result shows that the modulation of the thermal‐induced ET can be easily controlled by electronic effects of the ligands borne by the metal ions.…”
Section: Chemical Design Of Et Systemsmentioning
confidence: 61%
See 1 more Smart Citation
“…Therefore the Fe II site is stabilized. The two new squares 17 and 18 obtained with this new precursor display T 1/2 at 244 and 230 K, respectively, well above the T 1/2 at of 177 K found in the original square 2 . This result shows that the modulation of the thermal‐induced ET can be easily controlled by electronic effects of the ligands borne by the metal ions.…”
Section: Chemical Design Of Et Systemsmentioning
confidence: 61%
“…They concluded that the value of Δ E determined as 0.41 V allows the observation of thermally‐induced ET in 9 . A second study using electrochemistry as a guide to tune the ET behavior in squares was reported by Holmes et al in 2014 . In this work, a new Fe III building block was prepared by slightly modifying the complex used for the preparation of the original square.…”
Section: Chemical Design Of Et Systemsmentioning
confidence: 99%
“…Standard characterization of the compound has been conducted by ICP analysis ([Co]:[Fe]=1:1) and HRMS‐ESI(−) analyses (signals at m / z =1017.19 and 497.10 corresponding to {Na[{Co III {(Me) 2 (μ‐ET)cyclen}} 2 {(μ‐NC) 2 Fe II (CN) 4 } 2 ]} − and {[{Co III {(Me) 2 (μ‐ET)cyclen}} 2 {(μ‐NC) 2 Fe II (CN) 4 } 2 ]} 2− , respectively, are observed). The presence of signals in the 2000–2200 cm −1 IR range are associated with three types of cyanido ligands in the complex: axial (2051 cm −1 ), trans to bridge (2128 cm −1 ), and bridging (2146 cm −1 ) . In the same context, 13 C NMR of the sample in aqueous solution showed the signals corresponding to the ligand (56.9, 66.4, 67.1, and 71.5 ppm) plus three signals associated with the axial (175.6 ppm), trans to bridge (176.9 ppm), and bridging (185.1 ppm) cyanido groups (Figure S1 in the Supporting Information) .…”
Section: Methodsmentioning
confidence: 83%
“…Recently various multinuclear cyanide-bridged FeCo clusters exhibiting thermal and photoinduced charge transfers have also been synthesized [73][74][75][76][77][78] . The charge transfer process of FeCo compounds is expressed through a reversible phase transition between low-temperature phase with Fe II LS(S=0) -CN-Co III LS(S=0) and a high-temperature phase with Fe III LS(S=1/2) -CN-Co II HS(S=3/2) (Fig.…”
Section: Coupled Charge Transfer and Spin Transitionmentioning
confidence: 99%